2001
DOI: 10.1080/00140130010002008
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of perceptual and cognitive effects attributed to full-spectrum fluorescent lighting

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…It is likely that light can modulate learning, memory, and behavioral responses to learned cues in other paradigms. Although there is discrepancy in the field, several independent research groups have posited that a switch from regular fluorescent lighting, which emits light at only a few wavelengths, to full-spectrum lighting, which emits light across the visual spectrum, can result in improved mood and performance in the workplace and classroom (30). It is within reason, given our present results, that such a switch could have similar effects on learning and memory performance.…”
Section: Discussionmentioning
confidence: 58%
“…It is likely that light can modulate learning, memory, and behavioral responses to learned cues in other paradigms. Although there is discrepancy in the field, several independent research groups have posited that a switch from regular fluorescent lighting, which emits light at only a few wavelengths, to full-spectrum lighting, which emits light across the visual spectrum, can result in improved mood and performance in the workplace and classroom (30). It is within reason, given our present results, that such a switch could have similar effects on learning and memory performance.…”
Section: Discussionmentioning
confidence: 58%
“…Lighting. There is a large body of evidence in the psychology literature that lighting has an effect on mood and cognition [14,20]. It is hence unsurprising that lighting was found to have an effect on TAs' working environment.…”
Section: Corroborating Evidencementioning
confidence: 99%
“…Of course, because color experiences vary from individual to individual, it is not possible to know how another person experiences color [47]. Studies that have attempted to link colors with memory, mood, cognitive abilities, and personality found inconsistent results [48,49,50]. Also, some research findings suggested the opposite that color links to health and doctors can use colors of light to heal ailments [51].…”
Section: Color As An Attention Factormentioning
confidence: 99%